A retrospective study of dermatitis herpetiformis from an immunobullous disease clinic in north India. (11th May 2018) - Handa, Sanjeev; Dabas, Garima; De, Dipankar; Mahajan, Rahul; Chatterjee, Debajyoti; Saika, Uma N.; Radotra, Bishan D.
Abstract: Background: Indian data on dermatitis herpetiformis (DH) is not available. The aim of this study was to investigate the demographic and clinicopathological characteristics of patients with DH and to study its association with other autoimmune diseases. Methods: All data were collected from case record forms of patients registered in immunobullous disease clinic of our institute. The diagnosis was based on characteristic clinical and immuno/histopathological features. Results: A total of 65 patients were included, which constituted 9.47% of the registered patients in the immunobullous disease clinic over 3.5 years. The male to female ratio was 1.4 : 1; the average age was 44.35 ± 15.52 years. Direct immunofluorescence showed granular IgA deposits at the papillary tips in 83.07% and basement membrane zone in 12.3% patients. Sixteen (24.1%) patients had associated celiac disease, and 15 (23.07%) patients had other autoimmune comorbidities such as hypothyroidism. Forty percent of patients on strict gluten‐free diet achieved remission in 2 years, while 35.4% had frequent relapses as they continued gluten intake. Conclusions: Dermatitis herpetiformis is not a rare disease in northern India as previously believed. The clinical, histological, and immunopathological characteristics of Indian DH patients are similar to those reported in Caucasian populations. The limitations of our study include an absence of genetic testing for HLA‐DQ2 or DQ8, nonavailability of kits for detecting IgA specific for epidermal transglutaminase (IgA eTG), and short follow‐up period.